Forage and tuber yield and nutritional composition of Manihot esculenta Crantz meal with organic fertilization - Yam-Chale, Elda; Díaz-Echeverría, Víctor; Chavarría-Díaz, Addy; Oros-Ortega, Iván; Chay-Canul, Alfonso; Cen-Hoy, Amelia; Casanova Lugo, Fernando (Ecosistemas y Recursos Agropecuarios, 2018)
The objective was to evaluate the production and nutritional composition of cassava (Manihot esculenta Crantz) meal under dierent organic fertilization rates. Twenty 10 10 m plots were planted with cassava and fertilized with 0.0, 0.5, 1.0 and 1.5 kg plant-1  of sugarcane lter cake (part of the waste left after processing). The variables measured were fresh and dry forage yield (FFY and DFY), fresh and dry tuber yield (FTY and DTY), meal yield (MY) and their nutritional composition. The results indicate that the organic fertilization signicantly increased the FFY, DFY, FTY, DTY and MY compared to the control. Applying 1.5 kg of organic fertilizer signicantly improved crude protein content (CP, 3.37%). Organic fertilization with 1.5 kg plant-1 of compost improved forage and tuber yield, and CP content.